Teachers’ Engrossment in Professional Development in Surkhet Valley - Giri, Mukunda Kumar (Journal of NELTA Surkhet, 2015)
Since 2010, National Center for Educational Development (NCED) has extended teachers’ professional development program for in-service teachers to Resource Centre (RC) level while the service of the then 10 month teacher training was limited to Education Training Center (ETC) (NCED, 2011). All the secondary level teachers have got at least one opportunity to attend Teachers’ Professional Development (TPD) training in these last three years in Surkhet district. In institutional schools, teachers are deprived of such opportunities; however, they are seen equally potent and equally professional. On the other hand, if we compare teachers’ individual professionalism, we find much variation although there is same kind of opportunities given to them. With an assumption that the teachers are the main resources to be used in the school system, this article summarizes the survey carried out amidst teachers, to explain TPD and to reflect the situation of teachers’ engrossment in professional development initiatives (PDI) in Surkhet valley. This study has attempted to assess the situation of teachers’ engrossment in Teachers’ Professional Development Initiatives in Surkhet valley. Journal of NELTA Surkhet Vol.4 2014: 81-90